Pengaruh Penerapan Teknologi Informasi dan Audit Internal terhadap Efektivitas Pengendalian Internal Persediaan Pada PT Sejahtera Berkat Mandiri - Hutasoit, Marni; Riftiasari, Dinar; Ridwan, Achmad (Jurnal Informatika Ekonomi Bisnis, 2025)
This study is motivated by the ineffective internal control of inventory at PT Sejahtera Berkat Mandiri, which is attributed to the use of relatively basic technology and the suboptimal performance of internal auditors. This study aims to analyze the influence of information technology implementation and internal audit on the effectiveness of inventory internal control at PT Sejahtera Berkat Mandiri. The research is grounded in issues faced by the company, namely discrepancies between physical stock and system records, limited integration of information technology, and insufficient and non-comprehensive internal audit practices. A quantitative research method with a causal approach was employed. The study sample consisted of 75 respondents selected using total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression tests. The results show that the implementation of information technology significantly affects the effectiveness of inventory internal control, with a significance value of 0.000 and a regression coefficient of 0.827. Internal audit also has a significant influence on the effectiveness of inventory internal control, with a significance value of 0.000 and a regression coefficient of 0.461. Furthermore, the simultaneous implementation of information technology and internal audit significantly influences the effectiveness of inventory internal control, with a significance value of 0.000.